2016
DOI: 10.1182/blood-2016-05-712828
|View full text |Cite
|
Sign up to set email alerts
|

The risk of atrial fibrillation with ibrutinib use: a systematic review and meta-analysis

Abstract: Ibrutinib is an irreversible inhibitor of Bruton tyrosine kinase in the B-cell receptor signaling pathway. In randomized trials, ibrutinib is effective as first-line treatment of chronic lymphocytic leukemia (CLL)/ small lymphocytic lymphoma (SLL) (compared with chlorambucil), 1 for relapsed/refractory CLL/SLL (compared with ofatumumab or combined with bendamustine/rituximab), 2,3 or for relapsed/refractory mantle cell lymphoma (compared with temsiroliums), 4 with promising results in the treatment of Waldenst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(135 citation statements)
references
References 24 publications
5
121
2
7
Order By: Relevance
“…[1][2][3][4][5] An increased rate of atrial fibrillation has been observed in clinical trials of ibrutinib. 37,38 While there is net benefit from anticoagulation in individuals from the general population with atrial fibrillation and additional stroke risk factors, the increased bleeding risk in ibrutinib-treated patients may alter the risk-benefit ratio of anticoagulant therapy for the prevention of stroke and systemic embolism. To our knowledge, there is no evidence regarding the stroke risk in ibrutinib-treated patients with atrial fibrillation or whether [39][40][41] Patients with an indication for warfarin were excluded from the later trials after high rates of bleeding were noticed in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] An increased rate of atrial fibrillation has been observed in clinical trials of ibrutinib. 37,38 While there is net benefit from anticoagulation in individuals from the general population with atrial fibrillation and additional stroke risk factors, the increased bleeding risk in ibrutinib-treated patients may alter the risk-benefit ratio of anticoagulant therapy for the prevention of stroke and systemic embolism. To our knowledge, there is no evidence regarding the stroke risk in ibrutinib-treated patients with atrial fibrillation or whether [39][40][41] Patients with an indication for warfarin were excluded from the later trials after high rates of bleeding were noticed in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Ibrutinib use is associated with atrial fibrillation (AF), with an incidence of 5% to 6% after 18 months on therapy [4][5][6] and up to 16% with longer follow-up. 2,7 Prompted by an episode of unexplained ventricular tachycardia (VT) in a patient taking ibrutinib, we hypothesized that ibrutinib use may be associated with ventricular arrhythmias (VAs).…”
mentioning
confidence: 99%
“…Cytogenetic analysis was available in 26 (96%) and 147 patients (91%) with PEL and AEL, respectively, and revealed higher frequency of complex karyotype among patients with PEL (96% vs 61%; P , .001). Among patients with PEL, median number of cytogenetic abnormalities was 20 (range, 9-47), and median number of cytogenetic clones was 2 (range, [1][2][3][4][5][6] Targeted sequencing was performed in 12 patients (44%) with PEL. The most frequently mutated gene was TP53, detected in 11 (92%) of 12 patients, followed by ASXL1 (G646fs*), PTPN11 (G503R) and DNMT3A (L798P), each present in 1 patient (8%).…”
mentioning
confidence: 99%
“…Generally the latter should be avoided given evidence of increased major bleeding with this combination, without ibrutinib 25 . A recent meta-analysis of published trial data on ibrutinib and bleeding demonstrates a 2.72 relative risk of any bleeding, and a trend toward increased major bleeding at 1.66 relative risk, despite being underpowered for this outcome 26 .…”
Section: Bleeding Diathesis And/or Need For Full Dose Anticoagulationmentioning
confidence: 99%
“…The best studied cardiac side effect of ibrutinib is AF, which occurs initially in about 6% of patients 2,3,26 , increasing to 10-15% over two years 29 . An analysis from four randomized registration trials identified risk factors for AF on ibrutinib as age > 65 and a prior AF history.…”
Section: Cardiac Effects Of Ibrutinibmentioning
confidence: 99%